A New Electric Hydraulic Actuator Adopted the Variable Displacement Pump. Issue 1 (9th November 2015) - Shen, Wei; Mai, Yunfei; Su, Xiaoyu; Zhao, Jinbao; Jiang, Jihai
Abstract: In this paper, a new type Electric Hydraulic Actuator(New EHA) adopted variable displacement pump is presented to enhance the dynamic response of EHA. This system combines the advantages of electric with hydraulic systems and it is easy to be integrated with the whole electric system, which is a promising tendency to save energy and enhance control performance. Firstly, the basic principle and the difference with the traditional EHA are introduced. Moreover, the mathematical model is constructed. Then, the controller by using the fuzzy algorithm is designed. Finally, the simulation and experiment for the New EHA are investigated, both of the results show the effectiveness of the New EHA.